Interpersonal and Family Communication in Health Behaviours: A Review of Associate Professor Li Crystal Jiang’s Lecture at MHM 2025 (The Journal of Medicine, Humanity and Media, 2025)
This paper presents key insights from Associate Professor Li Crystal Jiang's lecture on Interpersonal and Family Communication in Health Behaviours, delivered at the MHM 2025 Special Seminar Series. The lecture systematically examined health communication through four dimensions: (1) Dyadic Perspectives, analysing bidirectional interactions in physician-patient and family relationships; (2) Provider-Patient Communication, highlighting challenges like didactic communication styles and proposing empathy-based solutions; (3) Motivational Interviewing (MI), detailing its client-centered principles for behavioural change; and (4) Family Systems, exploring how Family Communication Patterns (FCP) and the Social Cognitive Approach shape health behaviours. The discussion integrated theoretical frameworks with applied contexts, including AI-assisted tools like Peking University’s EasyHealth program.
Keywords: Provider-patient relationship; Dyadic perspective; Motivational interviewing; Family communication patterns